Efficacy and Safety of Zhenwu Decoction in the Treatment of Diabetic Nephropathy: A Systematic Review and Meta-Analysis. (1st November 2022) - Lv, Xialin; Zhou, Min; Liu, Xiu; Xiang, Qin; Yu, Rong
Abstract : Objective . To perform a systematic evaluation of the clinical efficacy and safety of Zhenwu decoction (ZWD) for the treatment of diabetic nephropathy (DN). Methods . PubMed, the China National Knowledge Infrastructure (CNKI), the China Science and Technology Journal Database (VIP), the Chinese Biomedical Literature Database (CBM), and the WanFang databases were searched, and a systematic review and meta-analysis of randomized controlled trials (RCTs) were subsequently conducted to compare the efficacy and safety of ZWD combined with conventional Western medicine (CWM) to conventional therapy alone in the treatment of DN. The Cochrane Handbook for Systematic Reviews of Interventions and GRADE criteria were utilized to assess the quality of the included literature, and RevMan 5.3 software was used for statistical analysis. Results . 13 randomized controlled trials were included, involving 1347 patients with diabetic nephropathy assigned into two subgroups according to the disease duration. The results revealed that compared with conventional therapy alone, ZWD combined with CWM treatment significantly improved the total effective rate (OR = 3.88, 95% CI = (2.87, 5.26), P  < 0.00001). Furthermore, ZWD combination therapy also decreased fasting blood glucose (MD = −0.72, 95% CI = (−0.97, −0.48), P  < 0.00001), BUN (MD = −1.92, 95% CI = (−3.19, −0.64), P  = 0.003), 24-hour urine protein (MD = −0.48, 95% CI = (−0.57, −0.39), P  < 0.00001), and serum creatinine levels (MD = −51.17, 95% CI = (−66.95, −35.39), P  < 0.00001). However, there was no statistical significance in the effect of combination therapy on creatinine clearance (MD = −0.64, 95% CI = [−8.21, 6.92], P = 0.87). However, there was no statistical significance in the effect of combination therapy oncreatinine clearance (MD =−0.64, 95% CI=[−8.21, 6.92], P =0.87). Conclusion . ZWD combined with CWM outperformed conventional Western medicine in DN treatment. However, further investigations via multicenter RCTs with rigorous designs and higher quality are still warranted.